Integration of Tri Hita Karana in the Accountability of Religious Organizations: A Systematic Literature Analysis - Nida, Desak Rurik Pradnya Paramitha; Arianto, Dodik; Rasmini, Ni Ketut; Budiasih, I Gusti Ayu Nyoman (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2026)
Tri Hita Karana (THK) embodies values that not only serve as a philosophical foundation for Balinese life but have increasingly shaped accountability practices. This study explores accountability in religious institutions using a Systematic Literature Review (SLR) approach. Articles were collected through Google Scholar searches with the assistance of the Publish or Perish application, yielding 41 publications that met the eligibility criteria. All articles were analyzed thematically to identify patterns, approaches, and configurations of accountability within THK-based religious contexts. The findings provide a conceptual mapping that elucidates how THK values frame accountability practices and create space for the development of more contextual theoretical models. The results show that accountability practices in THK oriented organizations encompass financial management, reporting, customary governance, and spiritual accountability. Qualitative approaches such as case studies, phenomenology, and interpretive methods dominate the research landscape. Hindu values such as dharma, karma phala, and the Tri Hita Karana philosophy underpin transcendental accountability, which includes vertical responsibility to God (parahyangan) and horizontal responsibility to others (pawongan) and the environment (palemahan). However, reporting practices remain informal, inconsistent, and poorly documented. Research gaps were found in asset management and the development of contextual spiritual accountability models. This study recommends formulating an organizational accountability model that integrates THK values, local culture, and modern governance principles to enhance organizational legitimacy, transparency, and sustainability.